2021
DOI: 10.1590/0100-29452021658
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes during the growth and development of litchi fruit (Litchi chinensis Sonn.) grown in Vietnam

Abstract: Some of the changes in physiological indicators during the growth and development of litchi fruit grown in Vietnam were studied. The length and diameter of litchi fruits reached their maximum value at 10 weeks after anthesis. The content of chlorophyll in litchi peel reached its highest value at 6 weeks and decreased rapidly. The content of carotenoids was low in fruit formation and then increased rapidly until fruit ripening. The vitamin C content and reducing sugar content increased continuously and reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…sweet cherry and mulberry [31], strawberry cultivars [31,32], sunberry [33], peach and tomato [34], cherry tomato and peach [35], jamun [20], bilberry [38], litchi fruit [39], Kiwi fruit [40] and phalsa fruit [21]. The total sugars content usually alter with stages of fruit development that reaches to maximum during ripening [20,21,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…sweet cherry and mulberry [31], strawberry cultivars [31,32], sunberry [33], peach and tomato [34], cherry tomato and peach [35], jamun [20], bilberry [38], litchi fruit [39], Kiwi fruit [40] and phalsa fruit [21]. The total sugars content usually alter with stages of fruit development that reaches to maximum during ripening [20,21,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Samkumar et al [38] noticed elevated levels of sugars in ripe berries, with glucose and fructose dominating with low sucrose during fruit development. Trong et al [39] found that the reducing sugars in initial stages of litchi fruit were comparatively low which reached to 2.138% in two weeks. In 8 to 10 weeks fruiting period, reducing sugars increased quickly and reached to 14.237%.…”
Section: Variation In Total Sugar (%) In Mulberry Cultivarsmentioning
confidence: 99%
“…jamun [20], bilberry [38], litchi fruit [39], Kiwi fruit [40] and phalsa fruit [21]. The total sugars content usually alter with stages of fruit development that reaches to maximum during ripening [20,21,35,36].…”
Section: Variation In Total Sugar (%) In Mulberry Cultivarsmentioning
confidence: 99%
“…Litchi (Litchi chinensis) and longan (Dimocarpus longan) are members of the Sapindaceae family, originally distributed in southern China and nearby regions [1][2][3][4]. As important evergreen fruit crops, litchis and longans are widely grown in the tropical and subtropical regions across the world.…”
Section: Introductionmentioning
confidence: 99%